KARAKTER FORMAL BANGUNAN 01 KAMPUS UNY KARANG MALANG - Ikhwanuddin Ikhwanuddin (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
ABSTRACTThe Karangmalang campus of Jogjakarta State University is a continuously developed area. At least, it can be seen from the appearance of some new buildings in these area. It is a good thing, but in the other, some worries appear as those new buildings were designed imperfectly. It seems that those new buildings were designed in different sight one to another.. "Is it because of the fully unclear and incomplete guideline? ". The clear and complete guideline is an important aspect to arrange the area; lack of such guideline will cause a messy area or an illegible one. Legibility is one aspect that Lynch (1960) proposed to create a good area. To get knowledge about legibility of an area, an understanding on formal character is needed. This is an important reasonwhy this research must be done.The research used quantitative research method in positivistic paradigm.Each object is observed and the information is collected in form of sketch ofplan and building's fa9ades, and also photographs. The objects of researchwere six offices of Dean in Jogjakarta State University consist of FBS, FIK, FT,FIS, FMIPA and FIP Dean's offices. The information had been analyzed ingraphical and verbal forms followed by quantitative manner to identify thedominant aspects of formal character of each object.This research reveals some formal characters of dean's office building inJogjakarta State University area. Those formal characters are: a) the axis is strong, b) the symmetrical form is very strong, c) the proportion is 1:3, d) the roof angle is 30 Q and 35Q, e) the hyrarcy is on one level in horizontal as well asvertical direction, f) the rythm is "a-b-c-b-a " pattern, and g) the dominant datumis ventilation hole.Keyword: legibility, formal character, the dean's offices building